Personality and situational judgement tests of leadership effectiveness : the mediating effect of motivation to lead - Heng, Wen Jun (Nanyang Technological University, 2020)
Given the importance of leadership to organizations, both researchers and practitioners are always in search of the best approach to identify and select effective leaders. Personality is one construct that has frequently been studied in relation to leadership outcomes. However, the past research in this domain is limited by the predominant use of the five-factor model to define personality (Extraversion, Agreeableness, Conscientiousness, Openness, and Neuroticism). Additionally, among the studies that have examined leadership effectiveness, few have used measures from selection processes, such as situational judgement tests, as a measure of leadership effectiveness. This study addresses these research gaps by examining the effect of socially adaptive (Sincerity, Fairness, Modesty, Greed avoidance, Humanism, Kantianism, and Faith in Humanity) and socially aversive (Machiavellianism, subclinical narcissism, and subclinical psychopathy) personality traits on situational judgement tests of leadership effectiveness. Further, the possibility of Motivation to Lead (MTL) as a mediator to the relationship was explored. Self-reported questionnaires on the personality traits and MTL, along with six situational judgement tests, were completed by 175 participants. Differences in scores on some socially adaptive and aversive personality traits were found for three of the situational judgement tests, while affective identity MTL mediated the relationships between narcissism and leadership effectiveness, as well as between modesty and leadership effectiveness. These results show that socially adaptive and aversive personality traits may have impact on leadership effectiveness, but the underlying mechanisms between these constructs can be better understood. Implications, limitations, and directions for future studies are discussed in the paper.